Anaplastic hemangiopericytoma manifesting as a rapidly enlarging extracranial mass lesion - Otani, Naoki; Nawashiro, Hiroshi; Wada, Kojiro; Minamimura, Kenzo; Takeuchi, Satoru; Shima, Katsuji (Asian Journal of Neurosurgery, 2012)
We, herein, present a patient with a recurrent anaplastic hemanigiopericytoma manifesting as a rapidly enlarging extracranial mass lesion, which was revealed by pathological and intraoperative findings. In practice, this case highlights the mandatory need for a careful long-term follow-up for patients with hemangiopericytoma, since recurrence with a greater degree of malignancy can develop following an extended disease-free interval, as such knowledge will be helpful for planning the optimal surgical procedures.
Keywords: Anaplastic hemanigiopericytoma; brain tumor; gamma knife radiosurgery; meningeal neoplasm